The Harlem Renaissance : a historical exploration of literature - Domina, Lynn (Santa Barbara, California : Greenwood, 2015)
"A perfect guide for use in high school classes, this book explores the fascinating literature of the Harlem Renaissance, reviewing classic works in the context of the history, society, and culture of its time"--
I. Introduction and background to the Harlem Renaissance -- II. Chronology -- III. The poetry of Claude McKay and Langston Hughes -- IV. Cane -- V. Passing and quicksand -- VI. Their eyes were watching God.
Includes chronology, discussion questions, suggested readings, and index.
Keywords: American literature -- African American authors -- History and criticism; Harlem Renaissance; Literature and society -- United States -- History -- 20th century; African Americans in literature; Harlem (New York, N.Y.) -- Intellectual life -- 20th century